The dose-dependent pteryxin-mediated molecular mechanisms in suppressing adipogenesis in vitro. (July 2021) - Nugara, Ruwani N.; Oku, Hirosuke; Saitoh, Seiko; Inafuku, Masashi; Iwasaki, Hironori; Kumara, R.P.; Undugoda, L.J.S.; Lankasena, B.N.S.
Graphical abstract: Highlights: Pteryxin follow a dual mechanism to attenuate adipogenesis. Suppression of early or late adipogenesis decided by the pteryxin dose. PTX₂₀ regulated ERK1/2 signaling followed by acceleration in lipolysis. PTX₅₀ regulated AMPK pathway and carbohydrate metabolism to reduce obesity. Abstract: The aim was to perform an in-depth characterization of pteryxin in the anti-obesity related molecular mechanisms using 3T3-L1 preadipocytes. Cells were treated with pteryxin 20 (PTX20 ) or 50 (PTX50 ) μg/mL during cell differentiation or maintenance period. Pteryxin dose-dependently suppressed adipogenic gene network. PTX20 downregulated key lipogenic genes suppressing fatty acid synthesis allotting the anti-adipogenesis in the late adipocyte formation stage. PTX50 downregulated adipogenesis related genes, and accelerated lipolytic activity by repressing the adipocyte size marker gene, MEST. In addition to Wnt5a, PTX50 suppressed adipocyte differentiation through TGF-β/Smad3 signaling pathway with the maximum adiposity inhibition in the early stage of adipogenesis and regulated the carbohydrate metabolism. Pteryxin regulated phosphorylation of ERK1/2 and AMPK, and decreased p38 MAPK to repress the mature adipocyte formation. Overall, we have demonstrated the anti-adipogenic characteristics of pteryxin consistent to its dose. PTX50 may serve as a potential candidate to ameliorate adiposity and improve the carbohydrate metabolism.